Cutaneous melanoma: how does ultraviolet light contribute to melanocyte transformation?. (December 2008) - Walker, Graeme
Ascribing a causal role to ultraviolet radiation in melanoma induction is problematic, as the relationship between total lifetime sun exposure and melanoma risk is not as strong as for some other skin cancers. Epidemiological studies show that heightened melanoma risk is most associated with intermittent sunburns. Despite this, lesions can develop on anatomical locations receiving intermittent (e.g., the trunk) or chronic exposures (e.g., the head and neck). Individuals developing melanoma on truncal sites tend to have more nevi, suggesting that in addition to the differences in forms of sun exposure, there may also be innate variation that makes one more susceptible to one or other mechanism of melanoma development. Such differences may depend upon different responses at the time of exposure (e.g., pigmentation characteristics, DNA repair capability and melanocyte proliferative response), and/or the role of the skin microenvironment in limiting proliferation of a ''primed'' or mutated melanocyte during the latent period leading up to the appearance of a melanocytic lesion.